Are fish oil supplements as effective as gemfibrozil for decreasing elevated triglycerides?. Issue 8 (August 2015) - Holmes, John; Cole, Dylan; Anderson, Kelly; Placek, Mary; Reckon, Amie
Abstract : Evidence‐Based Answer : The answer is unclear. In patients with hypertriglyceridemia, omega‐3 fatty acid and fibric acid derivatives reduce triglyceride levels compared with baseline, but evidence is conflicting whether omega‐3 fatty acid supplementation is as effective as gemfibrozil (SOR: C, inconsistent RCTs with disease‐oriented outcomes).